(untitled) (Tạp chí Y học Cộng đồng, 2026)
Purpose: To evaluate the visual performance and contrast vision outcomes after implantation of Lucidis extended depth-of-focus (EDOF) intraocular lens (IOL) following cataract surgery. Materials and methods: This prospective, single-center study included 66 eyes from 52 patients undergoing cataract surgery with implantation of the Lucidis IOL (SAV-IOL SA, Switzerland). Uncorrected and corrected visual acuity at distance (5 m), intermediate (67 cm), and near (40 cm) were assessed at 1 week, 1 month, 3 months, and 6 months postoperatively. Contrast sensitivity, photic phenomena (halos and glare), and patient-reported outcomes were evaluated at 3 and 6 months. Statistical analysis was performed using SPSS version 20, with significance set at p < 0.05. Results: At 6 months after surgery, uncorrected distance vision was 0,07 ± 0,09 logMAR, intermediate vision was 0,18 ± 0,08 logMAR and near vision was 0,14 ± 0,1 logMAR. Post-corrected distance vision was 0,03 ± 0,06 logMAR, intermediate vision was 0,06 ± 0,09 logMAR and near vision was 0,05 ± 0,08 logMAR. A total of 95.5% of eyes showed a reduction of ≤3 lines in contrast sensitivity at 10%. Most patients achieved spectacle independence for distance and intermediate vision, while 15% required spectacles for near tasks. No halos were reported at 6 months, and glare was minimal and transient. Conclusion: The Lucidis EDOF IOL provides excellent visual outcomes across all distances, maintains contrast sensitivity, and minimizes photic phenomena, resulting in high patient satisfaction following cataract surgery.